Volatile but cue-laden: measuring agenda-setting in the online newspaper environment - Mustapha, Lambe Kayode; Wok, Saodah (University Malaya Press, 2015)
After more than four decades of charting a paradigmatic direction in media effects research, agenda-setting has witnessed and survived enormous challenges to its main thesis. Despite the unending efforts of scholars to explicate the theoretical and logical mechanisms of the theory, the ever dynamic milieu in which agenda-setting effects is being explored, creates additional research problems necessitates further exploration. The arrival of new media and the subsequent migration of legacy media into the virtual realm, is another instance of the challenges of agenda-setting as a theory that is capable of unpacking media effects. While some scholars believe in the efficacy of agenda-setting in the new media environments, others argue along an attenuation perspective. Although a number of empirical approaches have been deployed to establish the continual heuristic value of agenda-setting in the age of new media, little, if any, attempt has been made to synthesise the findings into a coherent body. This review provides clues on the salient-directing cues in online newspapers on the one hand, and the challenges of measuring agenda-setting effects of online newspapers on the other hand.